A new amphinomid polychaete ( Annelida : Polychaeta) from Western Mexico - Salazar Vallejo, Sergio I. (1987)
Linopherus kristiani n. sp. is described from 46 specimens collected sublitoraly (8-80m) off Manzanillo, Colima and intertidally in Bahía Concepción, Gulf of California. It was two pairs of eyes, enlarged cirri at setiger 2, branchiae present from setiger 3 and continued through 23 segments (range 15-28, SD=3.9) with variable number of terminal filaments (at right setiger 16, x =30, range 5-59, SD= 12.2). A modified key to all the species of the genus, comments on morphological variation and associated species are also included.